CONSTRUCTION AND VALIDATION OF ALGORITHM FOR TREATMENT OF PRESSURE INJURY. - Maiúme Roana Ferreira de Carvalho; Geraldo Magela Salomé; Lydia Masako Ferreira (Journal of Nursing UFPE / Revista de Enfermagem UFPE)
Objective: to construct an algorithm for the treatment of pressure injury. Method: this is a quantitative, prospective, descriptive and analytical study for the elaboration of the algorithm; a wide review of the literature was carried out. Thirty-eight specialist nurses participated in the validation of the algorithm. Results: Thirty-five (92.1%) participants favored the ability of the algorithm to support the treatment of pressure injury. All the questions presented in the algorithm of treatment of pressure injury contributed favorably to the internal consistency of the instrument (Cronbach's alpha = 0.880). The great percentage of 80% was obtained by the classification according to the staging of the lesion. Each question pointed to the instrument as a tool capable of assisting the professional in making decisions regarding the choice of therapy proposed. Conclusion: the algorithm in the validated version showed reliability for the treatment of pressure injury.